A study on the relationship between gas-geochemical field and tectonic fault activities in the rivermouth area of northwestern Gulf of Tonkin - Hung, Duong Quoc; Shakirov, Renat; Iugai, Iosif; Diep, Nguyen Van; Anh, Le Duc; Dong, Mai Duc; Nam, Bui Van; Telegin, Yury (Vietnam Journal of Marine Science and Technology, 2019)
The article mentions the results of the new analysis of gas-geochemical and high resolution shallow seismic data acquired by the sea surveys in 2016, which revealed a remarkable coincidence between the seabed gas anomalies at river mouth area of Gulf of Tonkin and the gas distortion/accumulation phenomena in the near-surface sediment layers, especially right above the large tectonic fault systems, such as Red river, Lo river and Chay river. The gas-geochemical analysis reveals the existences of thermogenic and metamorphic methane and carbon dioxide gases within the faults of Red river and on Cat Ba island, anomalies of helium and hydrogen as well as the “heavy” isotopic carbon signals of methane and carbon dioxide in the areas of near-surface active faults. These new results suggest the initial conclusions about the relationship between gas-geochemical field and tectonic fault activities in study area.